Radome electromagnetic theory and design - Shavit, Reuven 1949- (John Wiley & Sons Ltd., 2018)
Radome Electromagnetic Theory and Design explores the theoretical tools and methods required to design radomes that are fully transparent to the electromagnetic energy transmitted or received by the enclosed antenna. A radome is a weatherproof and camouflaged enclosure that protects the enclosed radar or communication antenna, and are typically used on a fixed or moving platform such as an aircraft, ship or missile. The author - a noted expert in the field - examines the theoretical methods that apply to all type of radomes: planar, conformal, airborne and ground based. The text offers a description of the various measurement methods that characterise the electrical parameters of a radome, and discusses their merits in terms of accuracy. This groundbreaking book brings together in one volume all the necessary theoretical tools to design radomes